2017
DOI: 10.3389/fmicb.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Bacterial Maintenance and Minimal Energy Requirements

Abstract: Microbes maintain themselves through a variety of processes. Several of these processes can be reduced or shut down entirely when resource availability declines. In pure culture conditions with ample substrate supply, a relationship between the maximum growth rate and the energy invested in maintenance has been reported widely. However, at the other end of the resources spectrum, bacteria are so extremely limited by energy that no growth occurs and metabolism is constrained to the most essential functions only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 47 publications
(190 reference statements)
4
103
0
2
Order By: Relevance
“…This agrees with a recent study by Kempes et al . () in which smaller, more energy starved Bacteria focus cellular energy on protein and nucleotide metabolisms, and Orsi et al . () which found that protein cycling accounts for a large percent of cellular activity at low metabolic rates.…”
Section: Resultsmentioning
confidence: 97%
“…This agrees with a recent study by Kempes et al . () in which smaller, more energy starved Bacteria focus cellular energy on protein and nucleotide metabolisms, and Orsi et al . () which found that protein cycling accounts for a large percent of cellular activity at low metabolic rates.…”
Section: Resultsmentioning
confidence: 97%
“…The relationship between community size and energy availability is believed to be the product of a basal power requirement (BPR), which refers to the minimum amount of energy required for basic repair and maintenance functions (Lever et al 2015, Jørgensen & Marshall 2016. Organic matter quality and quantity determine the energy flux available at a given sediment depth and age, and the BPR determines the theoretical upper limit of the community size that can be supported at this energy flux (Hoehler & Jørgensen 2013, Kempes et al 2017. Despite the strong energy limitations in the deep subsurface, amino acid racemization models suggest that vegetative cells must continually turn over their biomass during burial .…”
Section: Sediment Environmentmentioning
confidence: 99%
“…Despite the strong energy limitations in the deep subsurface, amino acid racemization models suggest that vegetative cells must continually turn over their biomass during burial . Active cells may, however, exist in a survival state, devoting their limited energy to the repair and synthesis of essential biomolecules rather than to cell division and growth , Lever et al 2015, Kempes et al 2017.…”
Section: Sediment Environmentmentioning
confidence: 99%
“…Once dormancy is initiated by starvation or resource limitation (Lennon & Jones, 2011), a cell's metabolism is reserved mostly to essential functions such as biomolecular repair and replacement, rather than to support growth (Kempes et al, 2017;Orcutt et al, 2013;Tijhuis, Van Loosdrecht, & Heijnen, 1993). "Maintenance" energy refers to the sum of the energetic costs of the activities that do not produce growth, but that are required to sustain life.…”
Section: Introductionmentioning
confidence: 99%